A Novel Reconfigurable Metasurface with Coincident and Ultra-Wideband LTL and LTC Polarization Conversion Functions - Guo, Zexu; Cao, Xiangyu; Gao, Jun; Yu, Huicun; Han, Jiangfeng; Yang, Huanhuan; Tian, Jianghao (Společnost pro radioelektronické inženýrství, 2019)
In this paper, a novel reconfigurable metasurface (NRM) with coincident and ultra-wideband linear-to-linear (LTL) and linear-to-circular (LTC) polarization conversion functions is proposed. The unit of the proposed NRM consists of superstrate, air layer, metal patch, substrate and metal ground successively. By loading micro-electro-mechanical system (MEMS) between two adjacent metallic via, the proposed NRM can realize LTL and LTC polarization conversion efficiently. Numerical simulation results reveal that the bandwidth of LTL and LTC polarization conversion are coincident from 5.7 GHz to 23.5 GHz (fractional bandwidth of 122%). It is worth mentioning that few metasurface in existing literature can achieve highly coincident and ultra-wideband LTL and LTC polarization conversion functions. Finally, measurement results are in accordance with simulation results.
Keywords: Reconfigurable; ultra-wideband; polarization conversion